2017
DOI: 10.5194/isprs-archives-xlii-4-w5-81-2017
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Role of National Digital Cadastral Database (Ndcdb) in Malaysia and for Land-Based Analysis

Abstract: ABSTRACT:This paper explains the process carried out in identifying the significant role of NDCDB in Malaysia specifically in the land-based analysis. The research was initially a part of a larger research exercise to identify the significance of NDCDB from the legal, technical, role and land-based analysis perspectives. The research methodology of applying the Delphi technique is substantially discussed in this paper. A heterogeneous panel of 14 experts was created to determine the importance of NDCDB from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Conversely, it should be noted that unlike the universally known survey-accurate DCDB, NDCDB is a survey-accurate database but explicitly stores cadastral survey dataset and with limited cadastre information except those essential for land registration. Nevertheless, it plays a significant role mainly when the concern of the spatial analysis involves the land and people relationship (Halim et al, 2017). However, unused or improper cadastral data handling for spatial analysis may lead to questionable and unreliable result (Chan, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, it should be noted that unlike the universally known survey-accurate DCDB, NDCDB is a survey-accurate database but explicitly stores cadastral survey dataset and with limited cadastre information except those essential for land registration. Nevertheless, it plays a significant role mainly when the concern of the spatial analysis involves the land and people relationship (Halim et al, 2017). However, unused or improper cadastral data handling for spatial analysis may lead to questionable and unreliable result (Chan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The overall multi-case study methodology is shown in Figure 1. The case-study was propositioned based on Statement 2, NDCDB's significant role in the land-based analysis that stated: "NDCDB can help provide the required result of a land-based spatial analysis when users understand its characteristics and know how to adopt it for spatial analysis correctly The Delphi technique was used to establish Statement 2, NDCDB's significant role in the land-based analysis and was elaborated in detail in their paper by Halim et al (2017). Consequently, adjustment was made on the statement to ease the case-study approach and was determined as; i) "Such methods of applying NDCDB are because user understands its characteristics"; and ii) "Such methods of applying NDCDB is because users know how to adopt it."…”
Section: Introductionmentioning
confidence: 99%